Analisis Persepsi Petani terhadap Perubahan Penggunaan Lahan Perkebunan ke Lahan Padi Sawah di Kelurahan Atula Kecamatan Ladongi Kabupaten Kolaka Timur - Gusti Ayu Indah Kusuma; Rosmawaty Rosmawaty; Wa Ode Yusria (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2023)
Plantations in the East Kolaka region are no longer productive, leading to a decline in production and even no production. The community has made their plantation land more effective to increase production output. This initiative has led to plans to change the use of plantation land into paddy fields in the region, supported by the government through the construction of the Ladongi dam. This change in land use has led to varying views and responses from each farmer. This study aims to understand the farmers' reactions to the change in land use from plantation land to paddy fields in East Kolaka. The population involved consists of all 39 farmers who have changed their land use from plantation to rice fields, and using the census method, 39 farmers were obtained as research samples. Data were collected from surveys, direct interviews with farmers, and literature from related agencies. The data were analyzed using descriptive statistical analysis with the Likert scale as the measuring tool. The results were grouped into several items with scoring values. The study's findings indicate that farmers' perceptions regarding the change from plantation to rice fields in East Kolaka Regency are positive, falling into the medium category with a score of 3.39.